COPRECIPITATION IN THE BARITE ISOSTRUCTURAL FAMILY: 1. BINARY MIXING PROPERTIES - Zhu C. (My University, 2004)
This study attempts to provide a theoretical evaluation of coprecipitation and fundamental data of binary mixing properties in the barite isostructural family. Mixing properties of binary solid solutions in the barite isostructural family were derived from evaluation of coprecipitation experiments and partitioning coefficients reported in the literature. The Margules parameters, W, for these binary systems correlate well through the relationship, W−0.003875(ΔḠn,M2+°−ΔḠn,Tr2+°)=1262ΔV+30 where ΔḠn° denotes the non-solvation contribution to the standard partial molal Gibbs free energy of formation for the major (M2+) and trace (Tr2+) aqueous ions, and ΔV is the molar volume mismatch between the two substituting end-members ΔV≡(VTrSO4°−VMSO4°)2VTrSO4°, and V° is the molar volume of end-member components. From this correlation, Margules parameters for the BaSO4-TrSO4 and SrSO4-TrSO4 binary systems, for which no experimental data are available, were estimated. Tr here stands for trace divalent metals and includes Cu2+, Co2+, Zn2+, Fe2+, Mn2+, Eu2+, Cd2+, Ca2+, Sr2+, Pb2+, and Ra2+. These estimated mixing properties allow predictions of miscibility gaps for the BaSO4-TrSO4 and SrSO4-TrSO4 binaries, and partitioning coefficients for Tr2+ between barite or celestine and aqueous solutions.
Keywords: barite